4-Chloro-N-o-tolylbenzamide - Saeed, Aamer (International Union of Crystallography, 2008)
In the molecule of the title compound, C(14)H(12)ClNO, the two benzene rings are close to coplanar [dihedral angle = 7.85 (4)°]. The amide N—C=O plane makes dihedral angles of 34.04 (4) and 39.90 (3)°, respectively, with the 4-chloro- and 2-methylphenyl rings. In the crystal structure, intermolecular N—H⋯O hydrogen bonds link the molecules into chains.